Re-expansion Pulmonary Edema - Prasenohadi Prasenohadi; Wahyu Subekti (Indonesian Society of Respirology (ISR), 2023)
Re-expansion pulmonary edema (RPE) is a rare complication of pleural puncture (thoracentesis) and chest tube insertion. The incidence of RPE is low (1%), but mortality can be up to 20%. The main pathophysiological mechanism is pulmonary edema due to increased permeability and increased hydrostatic pressure in the pulmonary capillaries. Risk factors include duration of lung collapse (>3 to 7 days), size of pneumothorax (>30%), volume of aspirated air or fluid (>1.5 to 3 L), excessive negative intrapleural pressure, diabetes mellitus, and chronic hypoxemia. Prevention includes limiting the volume of aspirated air or fluid (<1.5 L), air or fluid evacuation in a controlled manner, and preventing excessive negative intrapleural pressure. Treatment is supportive care through cardiovascular and respiratory monitoring, oxygen and decubitus positioning.